2020
DOI: 10.1037/int0000199
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the special issue: Supervisee perspectives of supervision processes.

Abstract: In this introduction to the special issue on Supervisee Perspectives of Supervision Processes, we overview salient extant research findings and provide a theoretical grounding to provide a supportive context for the collection of articles in this curated issue. The enclosed articles provide first person narrative examples of several extant research findings: clinical expertise unfolds developmentally; multiculturalism impacts supervision; the supervisory relationship is highly important; supervision can benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Students in both groups could therefore have benefited from the use of ROM, and in fact both groups yielded effect sizes on par with Reese and colleagues' feedback group. Decades of research have failed to demonstrate that supervision has a reliable impact on client outcomes (Watkins, 2011; however, see Callahan & Love, 2020), a liability in an era of accountability. ROM may enhance client outcomes in training settings, but more rigorous research is needed.…”
Section: Benefits Of Routine Outcome Monitoring In Psychology Trainingmentioning
confidence: 99%
“…Students in both groups could therefore have benefited from the use of ROM, and in fact both groups yielded effect sizes on par with Reese and colleagues' feedback group. Decades of research have failed to demonstrate that supervision has a reliable impact on client outcomes (Watkins, 2011; however, see Callahan & Love, 2020), a liability in an era of accountability. ROM may enhance client outcomes in training settings, but more rigorous research is needed.…”
Section: Benefits Of Routine Outcome Monitoring In Psychology Trainingmentioning
confidence: 99%
“…In contrast to supervision during graduate school, supervision of qualified professionals is usually self-selected, paid for by the supervisee, and less likely to involve emphasis on the acquisition of new skills. Empirical investigation of the effectiveness of supervision is a relatively nascent area of research (Callahan & Love, 2020;Milne et al, 2012) and is focused mainly on unlicensed trainees (e.g., see the systematic review by Wheeler & Richards, 2007). This means that little is known about how practicing psychologists use supervision or if they benefit from it.…”
Section: Supervisionmentioning
confidence: 99%
“…Some studies have reported strategies that trainees deem useful (e.g. Kelly and Hassett, 2021;Murr et al, 2020), but research examining trainee perspectives remains inadequate, and no firm conclusions can be made about what trainees want from supervision (Callahan and Love, 2020;Kelly and Hassett, 2021). Therefore, this study aimed to further explore what trainees believe is most and least helpful following each supervision meeting, and to determine whether trainees' perceptions of helpful supervision interventions align with what the expert consensus purports to be effective CBT supervision.…”
Section: Introductionmentioning
confidence: 98%
“…A strong supervisory alliance is crucial as it has been associated with increased trainee openness to disclose difficulties encountered with clients (Falender, 2014;O'Donovan and Kavanagh, 2014;Wilson et al, 2016). Supervisors must create an environment where trainees feel safe or comfortable discussing problems and mistakes, as effective supervision often depends on trainees' disclosure of their difficulties (Cartwright, 2019;Callahan and Love, 2020;Falender, 2014;Johnston and Milne, 2012;Mehr et al, 2010). This task can be difficult due to the inherent power differential within the dyad, which can lead to trainees experiencing fear of repercussions in terms of negative evaluations by their supervisors.…”
Section: Introductionmentioning
confidence: 99%